Associations of chronic diarrheal symptoms and inflammatory bowel disease with sleep quality: A secondary analysis of NHANES 2005–2010 - Zhang, Jingyun; Yu, Senhai; Zhao, Gang; Jiang, Xiaoyan; Zhu, Yimin; Liu, Zuyun (Frontiers in Neurology, 2022)
Abstract Objective: Poor sleep quality is highly prevalent in patients with chronic diarrheal symptoms or inflammatory bowel disease (IBD). This study aimed to evaluate the associations of chronic diarrheal symptoms and IBD with sleep quality in the general US population. Methods: 14696 adults (≥20 years) from the National Health and Nutrition Examination Survey (2005-2010) were included in the study. Chronic diarrheal symptoms and IBD were defined by self-reports. Sleep quality was assessed by sleep disorder, sleep trouble, and sleep duration. Multivariable logistic regression models were used to examine the associations. Results: After adjustment of a series of covariates, we found that participants with chronic diarrheal symptoms or IBD had higher odds of sleep disorder (chronic diarrheal symptoms: odds ratio [OR]=1.20, 95% confidence interval [CI]=1.04-1.38; IBD: OR=3.86, 95% CI=1.92-7.77) and sleep trouble (chronic diarrheal symptoms: OR=1.19, 95% CI=1.09-1.30; IBD: OR=2.32, 95% CI=1.30-4.14), respectively. Sleep duration for participants with IBD was significantly shorter than that for those without IBD (β=-0.39, 95% CI=-0.78-0.01, P=0.045). Subgroup analyses revealed that the associations of chronic diarrheal symptoms and IBD with sleep disorder and sleep trouble were more pronounced among women. Conclusions: In this large sample of US adults, we found that chronic diarrheal symptoms and IBD were significantly associated with sleep quality, particularly in women. The findings highlight the importance of managing bowel health to promote high quality of sleep; and thus, improve quality of life in this subpopulation.